Estruturas de governança em sistemas de cafés certificados : um estudo entre produtores e cooperativas no sul de Minas Gerais - Gonçalves, Luciana Angelino (2014)
The production and consumption of certified coffee double every year in Brazil, and the state of Minas Gerais is the largest producer. There are different patterns of certifications in coffee sector, not only in individual properties, but also in cooperatives. Cultural and legal changes in the certified coffee sector influences in the alignment, dynamic and transactions, between agents involved, in this case, cooperatives and producers, through changes in Institutional Environment, driving actions in the Organizational Environment. In this context, this study aimed to understand the design of governance structures between certified coffee producers and cooperatives in the South of Minas Gerais. Regarding the theoretical approach, it encompassed studies related to coordination mechanisms and agent behavior, based on the Theory of Economics Transaction Costs (ETC), the Resource-Based-View (RBV), and the complementarities of both approaches, according to resources and attributes involved in the certifications. Methodology comprised a qualitative descriptive research, conducted through on semi-structured interviews as a tool for data collection, through content analysis. As the result of the objective proposed, it were identified attributes, resources and capabilities, in governance structures "market", comprised in: "unsecured market" and "secured market" due to the "sunk costs" involved. Uncertainty asset specificity, in the dynamics of the certified coffee market, proved to be decisive for the understanding of these governance structures, indicating complementarities between RBV and TCE. The more complex and rigid the process of certification among agents, the higher the efforts to measure and safeguard investments involved in the transaction with the cooperative, due to the presence of sunk costs. The presence of asymmetric information does not allow agents to warranty of all transaction costs, resources and expertise, as well as the measurement of resources stemmed from "Ricardian rents." However, the governance structure of "unsecured market," not diminish risks of "quasi-rent" appropriation among agents for more complex certifications, revealing misalignments and market failures. It is evident that even if there is a 'relational backgrounf "behind the transactions between these agents to be" cooperative ", arrangements through market still predominates . Due to the competitiveness in this industry, this can lead to unsustainability of these relationships if more complex agreements are not signed, tending to hybrid contracts with greater assurance.